(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
The first objective of this paper is to summarize the content of financial theory,as it is explained in business schools, their strengths and weaknesses, proposingways to overcome the latter, specially taking into account the crisis that began in2007. It also gives a more comprehensive analysis of the origins and the ways toovercome the crisis. And the emphasis is put on ethical failures and how to solvethem. The main thesis in that, with what we have learned in seven years of crisis,there are many things that need to be improved.